KUALITAS PROTEIN KASAR, SERAT KASAR, DAN KADAR ABU AMOFER DARI KOMBINASI JERAMI PADI DAN JERAMI JAGUNG - Aldi Hariswan; Fridarti Fridarti; Sri Mulyani; Halimatuddini Halimatuddini (Jurnal Peternakan Tamansiswa, 2026)
The purpose of this study was to determine the effect of amofer from a combination of rice straw and corn straw on the quality of crude protein, crude fiber, and ash content. The design used was CRD (Completely Randomized Design) which consisted of 5 treatments and 5 replications namely P1 (500 g rice straw), P2 (500 g corn straw), P3 (350 g rice straw + 150 g corn straw), P4 (250 g rice straw + 250 g corn straw), P5 (150 g rice straw + 350 g corn straw). Variety analysis shows that the quality of crude protein, crude fiber, and amofer ash content of the combination of rice straw and corn straw have a very significant effect (P<0,01) to increase crude protein and decrease crude fiber and ash. The results of this study concluded that amofer from the combination of 350 g cron straw and 150 g rice straw was the highest percentage of crude protein. Sigle amofer and cron straw can reduce crude fiber content and ash content.